Bacopa monnieri (L.) Wettst. plant extract mediated synthesis of metallic nanoparticles and regulation of bacoside-A- memory enhancer compound and their application: A comprehensive review - Abhishek Dadhich; Rohit Jain; Madan Mohan Sharma (Plant Nano Biology, 2025)
Bacopa monnieri L. Wettst. (BM) is a well-known medicinal plant that has recently gained attention for its potential in the synthesis of metallic nanoparticles (NPs), including silver (Ag), copper (Cu), zinc (Zn), and gold (Au). These nanoparticles also influence the production of bacoside-A, a compound known for its memory-enhancing effects. This review focuses on the green synthesis of these metallic NPs using BM extracts, examining how nanoparticles stimulate the production of secondary metabolites, particularly bacoside-A. When exposed to nanoparticles, BM plants experience oxidative stress, which activates critical biosynthetic pathways such as the MEP (methylerythritol phosphate) and MVA (mevalonate) pathways, both of which are essential for the synthesis of bacoside-A and other terpenoids. Nanoparticles also enhance the activity of enzymes like DXS (1-Deoxy-d-xylulose 5-phosphate synthase) and HMGR (3-Hydroxy-3-methylglutaryl coenzyme A reductase), leading to the increased production of bioactive compounds. Additionally, the stress induced by nanoparticles elevates gene expression related to plant defense mechanisms, further boosting secondary metabolite synthesis. The review also highlights the potential therapeutic benefits of these nanoparticles, particularly in the fields of antimicrobial, anticancer, and neuroprotective treatments. Nanoparticles enhance the bioavailability and effectiveness of therapeutic agents, making them a valuable tool in biomedical applications. The integration of nanotechnology with plant-based medicine shows significant promise for advancing pharmaceutical and biomedicine research. However, future studies are necessary to optimize the synthesis of nanoparticles, investigate the molecular mechanisms of plant-nanoparticle interactions, and scale up production for broader industrial and clinical applications.